Systemic administration of a nanoemulsion with tributyrin reduces inflammation in experimental colitis. Issue 2 (30th April 2015) - Leonel, Alda Jusceline; Silva, Elton Luiz; Aguilar, Edenil Costa; Teixeira, Lilian Gonçalves; Oliveira, Rafael Pires; Faria, Ana Maria Caetano; Cara, Denise Carmona; Ferreira, Lucas Antônio Miranda; Alvarez‐Leite, Jacqueline I.
Abstract : Tributyrin (TBT) is a triacylglycerol formed by three molecules of butyrate that is able to improve colonic mucosal lesions and inflammation when given orally or as an enema. The effects of systemic TBT administration in inflammatory bowel disease (IBD) have been less well studied. We prepared a nanoemulsion containing tributyrin (nTBT) and studied its effects on a model of dextran sodium sulfate (DSS)‐induced colitis. Mice were kept in the experiment for 15 days. Animals in the Colitis group received DSS (2.5% in their drinking water), whereas Control mice received only water during the last 7 experimental days. Animals were injected intraperitoneally (IP) with a nanoemulsion lacking TBT (Control and Colitis group) or containing TBT (Control nTBT and nTBT‐Colitis) every other day for 15 days. Colonic mucosal damage and cytokine concentration were assessed by histopathological score and ELISA, respectively. Inflammatory infiltrates were assessed by enzymatic assay, and leukocyte rolling and adhesion in the colonic circulation were determined by intravital microscopy. Results revealed that the colonic architecture was not modified by nTBT administration. However, the colons of nTBT‐Colitis mice presented reduced eosinophilic and neutrophilic infiltration associated with increased TGF‐β concentrations compared to those of the Colitis group. Leukocyte rolling and adhesion were reduced in the nTBT‐Colitis group, suggesting a systemic anti‐inflammatory effect of nTBT. In conclusion, our results show that nTBT administered intraperitoneally is effective in reducing DSS‐induced inflammation, whereas the trophic effects described with oral or local administration of TBT were not present when it was injected systemically. Practical applications: In this study, we show that the intraperitoneal administration of a nanoemulsion with tributyrin (nTBT) is able to reduce the inflammation observed in DSS‐induced colitis. Due to its anti‐inflationary actions, nTBT could be used in the future as a potential auxiliary drug in the treatment of inflammatory bowel diseases as well as other disorders with a systemic (low‐grade) inflammatory component such as atherosclerosis and obesity. Nanoemulsion of tributyrin (nTBT) reduces inflammation related to DSS induced colitis. The determination of macrophage (i), neutrophil (ii), and eosinophil (iii) infiltration in colon and intravital microscopy of mesenteric vessels showing the rolling (iv) and the adhesion (v) of total leukocytes in the colons of mice from the Control group receiving water and a nanoemulsion lacking tributyrin, the nTBT group receiving water and nanoemulsion with nTBT, the Colitis group receiving DSS and a nanoemulsion lacking tributyrin, and the Colitis nTBT group receiving DSS and nTBT. Different letters indicate p  < 0.05. Abstract : Nanoemulsion of tributyrin (nTBT) reduces inflammation related to DSS induced colitis. The determination of macrophage (i), neutrophil (ii), and eosinophil (iii) infiltration in colon and intravital microscopy of mesenteric vessels showing the rolling (iv) and the adhesion (v) of total leukocytes in the colons of mice from the Control group receiving water and a nanoemulsion lacking tributyrin, the nTBT group receiving water and nanoemulsion with nTBT, the Colitis group receiving DSS and a nanoemulsion lacking tributyrin, and the Colitis nTBT group receiving DSS and nTBT. Different letters indicate p  < 0.05.